Alkaline-Earth Metal Complexes: Mixed Ligand Complexes of Alkaline-Earth Metal Salts of Some Organic Acids with 2-Methyl-Oxine - Prakash, Dharam; Kumar Yadav, Ashok (Asian Journal of Chemistry, 2010)
A number of mixed ligand complexes of alkaline-earth metal salts of some organic acids like 1-nitroso-2-naphthol (1N2N), o-nitrophenol (ONP), 2,4-dinitrophenol (DNP), salicylaldehyde (Sal-H) and salicylic acid (Sal·A) with 2-methyl-oxine have been synthesized and characterized by elemental analysis, conductivity measurement and FTIR-spectral studies.